Thymus Ontogeny in Frogs: T-Cell Renewal at Metamorphosis - Rollins-Smith, Louise A. (Hindawi Publishing Corporation, 1992)
Metamorphosis in amphibians presents a unique problem for the developing immune system. Because tadpoles are free-living, they need an immune system to protect against potential pathogens. However, at metamorphosis, they acquire a variety of new adultspecific molecules to which the tadpole immune system must become tolerant. We hypothesized that Xenopus laevis tadpoles may avoid potentially destructive antiself responses by largely discarding the larval immune system at metamorphosis and acquiring a new one. By implanting triploid (3N) thymuses into diploid (2N) hosts, we examined the influx and expansion of host T-cell precursors in the donor thymus of normally metamorphosing and metamorphosis-inhibited frogs. We observed that donor thymocytes are replaced by host-derived cells during metamorphosis, but inhibition of metamorphosis does not prevent this exchange of cells. The implanted thymuses export T cells to the spleen. This donor-derived pool of cells declines after metamorphosis in normally developing frogs but is retained to a greater extent if metamorphosis is inhibited. These studies confirm previous observations of a metamorphosis-associated wave of expansion of T cells and demonstrate that it is not dependent on the relatively high concentrations of thyroid hormones required for metamorphosis. Although some larval T cells persist through metamorphosis, others may be destroyed or the larval population is significantly diluted by the expanding adult population.